Complete IELTS. Bands 6.5-7.5. Student's Book with Answers - Brook-Hart G. Guy (Cambridge English)
Complete lELTS Bands 6.5-7.5 is a brand new course to prepare students for the lELTS test at an advanced level (CI). It combines the very best in contemporary classroom practice with stimulating topics aimed at young adults. It is designed to equip students to perform at their very best and provides strategies and skills to maximise their score. The information, practice and advice contained in the course ensure that they are fully prepared for all parts of the test. Informed by Cambridge's unique searchable database of real exam papers, the Cambridge English Corpus, Complete lELTS Bands 6.5-7.5 includes examples and exercises which tackle key lELTS problem areas at this level, making it the most authoritative lELTS preparation course available. Complete lELTS Bands 6.5-7.5 Student's Book with Answers features: 8 topic-based units, providing language input and practice for each of the four papers of the lELTS test a step-by-step approach to completing the most challenging Reading and Listening fasks; help in generating and expressing complex ideas for Writing and Speaking tasks; Key grammar and Vocabulary sections a Language reference which develops advanced-level vocabulary and assists students in producing precise and accurate grammar. Writing and Speaking references complete with tasks, sample answers and exercises a full lELTS practice test advice on timing and technique, which equips learners to complete every section of the test in the time available a CD-ROM for self-study.